Water vapor sorption on Marcellus shale: measurement, modeling and thermodynamic analysis. (1st December 2017) - Tang, Xu; Ripepi, Nino; Valentine, Katherine A.; Keles, Cigdem; Long, Timothy; Gonciaruk, Aleksandra
Highlights: Water vapor ad/de-sorption isotherms in Marcellus shale were measured. Temperature-dependency hysteresis of water vapor ad/de-sorption isotherms were observed. Dent's model can describe water vapor adsorption isotherms in shale. A new method is developed to calculate isosteric heat of adsorption for water vapor adsorption in shale. Abstract: Water vapor ad/desorption isotherms were measured for a Marcellus shale at 303.15 K, 313.15 K and 328.15 K and a relative vapor pressure up to 0.95 to investigate the adsorption behavior of water on shale. Dent's multilayer model was applied to fit three measured adsorption isotherms simultaneously using a global fitting approach. This model can also be used to estimate the primary and secondary adsorption sites for water on shale. The difference between the adsorption and desorption isotherms under different temperatures showed a similar hysteresis loop with a temperature-dependency feature. Based on the successful application of the Dent's multilayer model, the isosteric heat of adsorption are calculated analytically, unlike the routinely used Clausius–Clapeyron approximation. By this method, the temperature dependence, as well as the uptake dependence of the isosteric heat, can be readily investigated. Using the ideal gas law will result in an overestimation of the isosteric heat of adsorption at high vapor pressure conditions. This work therefore not only discloses the temperature-dependency feature of the hysteresis behavior, but justifies the method for modeling water vapor adsorption isotherms and obtains the corresponding isosteric heat of adsorption laying the foundation for future investigation of the interaction between water and shale to optimize shale gas development.